Studies on preventive and curative ethnoveterinary remedies applied by the Rendille/Ariaal and Gabra Communities of Marsabit district , Kenya. - Wamwere-Njoroge, George J. (University of Nairobi, 2004)
This study was undertaken to take stock of the existing traditional veterinary knowledge and practices among the Rendilie/Ariaal and Gabra ethnic groups of Marsabit District and to determine the antibacterial activity of some of their herbal remedies after water and ethanol extraction. Increasing alternatives for prophylactic and therapeutic inputs and services against livestock diseases/ailments among the resource poor pastoral communities of Marsabit District was the main objective of ,the work. The specific objectives were 1) Identification of livestock traditional healers (LTHs) among the Rendille/Ariaal and Gabra communities of Marsabit District and assessment of the level of existing veterinary knowledge (EVK) and practices; 2) collection, documentation and botanical identification of the plant species and materials that were considered usable for managing livestock diseases by the study communities; 3) screening of all the medicinal plants cited for antibacterial activity. The inventorized data were collected through participatory rural appraisal (PRA) workshops at the "Manyatta" level and residential workshops for specifically identified livestock traditional healers (LTHs). Some of the outputs from the PRAs were lists of renowned LTHs and crude data on the ethnoveterinary knowledge (EVK) as viewed by the general public. In addition, lists of important livestock diseases per species among the study communities were also generated at the manyatta workshops. The PRA workshops identified the renowned LTHs, who were used to fine-tune the raw data documented during the manyatta PRAs. The LTHs also collected herbal plants voucher specimens for sensitivity tests and for botanical identification. The well and disc reservoir methods for antibacterial sensitivity tests were used with water and ethanol as the extracting solvents. Micrococcus lutea and Bacilus cereus were used as the test microorganisms grown on Muller-Hinton agar. In total, 72 plant species in 34 families were inventorized as medicinal plants applied by the two communities in the prevention and cure of more than 20 livestock diseases. Some non-plant-based folk veterinary practices were also documented and induded salty soils and salty waters. In addition, manipulative techniques were also reportedly applied in traditional management of diseases and other animal ailments. These included surgical intervention, branding, and general massage. Burseraceae, Caparidaceae, Euphorbiaceae, Mimosoideae and Solanaceae were the five most common plant families used by the two communities. These 5 plant families accounted for 22 of the 72 medidnal plant species identified. Most of the diseases/ailments treated using the plant, the nonplant- based and/or manipulative indigen?>us veterinary remedies were divided into six broad but distinct categories, namely, digestive disorders; respiratory disorders; traumatic extemal injuries and ectoparasites; reproductive problems and infertility; eye infections; and mineral defidencies. There were more Gabra pastoralists (82%) who used indigenous remedies as their first line of treatment than were Rendilie/Ariaal pastoralists (59%) who also used indigenous remedies as their first line of treatment. Women appeared to play an insignificant role as LTHs as only 3 out of the 30 LTHs (10%) identified from the Gabra community and 4 out of the 24 LTHs (17%) from the Rendille/Ariaal community were women. Specialization of the LTHs from both communities was evident Areas of specialization induded general practioners, bone setters, camel diseases specialists and specialists on camel dystocia and infertility. Sensitivity tests revealed that some of the herbal plants used by the two communities had very high antibacterial activity. Out of the 72 plant species cited as medicinal by both study ethnic groups, only 36 (50%) were available for screening for antibacterial activity. Out of these, 21 were from Rendille/Ariaal community and 15 from Gabraland. Roots of Terminalia brownii from Rendille/Ariaal region showed the highest activity against M. lutea, with an inhibition zone (diameter) of 24mm and 25mm with ethanol and water extracts, respectively, using the disc reservoir method. Using the well reservoir method, the roots of the same herb showed an inhibition zone of 24mm and 23mm with ethanol and water extracts, respectively. Water extract of Balanites aegyptiaca leaves from Gabraland using the disc reservoir method gave an inhibition zone of 10mm and 7m~ against B. cereus and M. lutes, respectively. Under the same extraction method, fruits/seeds of Solanum incanum showed inhibition zones of 9mm and 9mm for B. cereus and M. lutea respectively. Of the 15 medicinal plants from Gabraland, an extract of whole shrub of Cucumis dipsaceus gave the highest inhibition zone (14mm) with B. cereus compared 7mm showed by M. lutea after ethanol extraction in well reservoir method. The water extraction of Commiphora flaviflora stem gave 10mm and 9mm against B. cereus and M. lutea, respectively. Based on these findings, it is concluded that rich traditional veterinary practices among the Rendilie/Ariaal and Gabra communities of Marsabit District exist and that some of the medicinal plants used by these ethnic groups contain demonstrable antibacterial activity. Given that modem veterinary drugs are not likely to be readily available to these communities in the near future, there is a need to conduct clinical trials using the indigenous remedies in an effort to asses their efficacy and to develop dosage recommendations of the proven ones. This will offer alternatives to modem veterinary inputs, leading to improved animal health care delivery for the resource poor pastoralists of Marsabit District and other ASAL areas of Kenya.